ISOLATION AND BIOCHEMICAL CHARACTERIZATION OF PASTEURELLA MULTOCIDA AND GALLIBACTERIUM ANATIS STRAINS IN POULTRY WITH RESPIRATORY SIGNS - Castillo, Gonzalo (2014)
The aim of the study was to identify biovars of Pasteurella multocida and Gallibacterium anatis in poultry with respiratory signs. These bacteria were isolated from samples of secretions and organs of affected broilers, layers and ducks from various poultry farms in the coast and the tropics of Peru. Out of 25 isolates obtained, 13 strains of P. multocida and 12 of G. anatis were identified based on culture characteristics, morphology and biochemical tests (oxidase, catalase, indole, urease). These strains were subjected to micro-well fermentation tests with 10 carbohydrates and one amino acid for typification. Results showed that eight strains of P. multocida corresponded to biovar 1 and the others to biovars 3, 4, 6, 10 and 11, while 11 strains of G. anatis corresponded to biovar haemolytica and one strain to biovar anatis.